Impact of Tropical Hardwoods Campaign - Mohamad, Rusli (Universiti Putra Malaysia Press, 1996)
A survey was conducted to assess the awareness of the tropical hardwoods campaign and its impact on exports of timber products from Peninsular Malaysia. Information was obtained from the questionnaire answers of thirty-two exporters, from one hundred contacted. There is a high degree of awareness of the tropical hardwoods campaign among the exporters. The same level of awareness is not shown for boycott and certification of tropical timber products. There is no difference in awareness of certification of tropical timber products among the exporters. However, exporters to Europe and in particular to the Netherlands are more aware of the campaign to boycott tropical timber products than exporters to other destinations. Exporters to the Netherlands are more likely to report that their exports are adversely affected by the tropical hardwoods campaign. A majority of exporters feel that the tropical hardwoods campaign is less serious than the problem of diminishing log supply that they are currently facing.